Virulence and Drug-Resistance of Staphylococcus aureus Strains Isolated from Venous Ulcers in Polish Patients - Gajda, Mateusz (Int J Environ Res Public Health, 2021)
Infected chronic venous ulcers (VUs) represent a major health problem. We analysed the aerobic microbiome in the VUs, the virulence, and drug-resistance of Staphylococcus aureus (SA) strains. Swabs from 143 outpatients and inpatients Polish subjects were collected. SA strains were tested for drug sensitivity using a phenotyping method and for methicillin-resistant SA (MRSA) and macrolide-lincosamide-streptogramin B (MLSB) resistance using PCR. We analysed virulence genes, the genetic similarity of strains, and performed Staphylococcal cassette chromosome mec typing and Staphylococcal protein A typing. SA was isolated as a single one in 34.9% of cases, 31.5% paired with another pathogen, and 33.6% S. aureus combined with at least two other strains. The majority of SA isolates (68.5%) possessed the virulence lukE gene. Drug resistance was significantly common in hospitalised than in ambulatory patients (OR 3.8; 95%CI 1.8–7.91). MLSB (altogether in 19.6% isolates) were observed mostly in non-hospitalised patients (OR 9.1; 95%CI 1.17–71.02), while MRSA was detected in 11.9% of strains equally. Hospitalisation and patient’s age group (aged > 78.0 or < 54.5 years) were significant predictors of the multi-drug resistant SA (MDR-SA). Over 30% of the infected VUs were associated with multi-species biofilms and presence of potentially highly pathogenic microorganisms. Elderly hospitalised patients with chronic venous ulcers are prone to be infected with a MDR-SA.